Efficacy of estrogen-progestogen therapy for women with vascular retained products of conception following miscarriage or abortion - Munekage Yamaguchi; Akiho Nishimura; Takeshi Motohara; Takashi Ohba; Eiji Kondoh (Elsevier, 2023)
Objective: To assess the clinical characteristics and endocrinological background of women with vascular retained products of conception (RPOC) after miscarriage or abortion and evaluate the effect of estrogen-progestogen therapy (EPT) as an initial treatment on this population based on their endocrinological background. Materials and methods: Women with vascular RPOC after miscarriage or abortion at less than 20 weeks of pregnancy who were given EPT (conjugated estrogen and norethisterone) were retrospectively reviewed. Their clinical characteristics, hormonal parameters, ultrasonographic findings, and outcomes were evaluated. Results: Of 35 women with vascular RPOC, 30 (86%) presented with vaginal bleeding at a visit, and 6 (17%) required inpatient management due to heavy bleeding. Among women who presented with vaginal bleeding, serum progesterone levels were significantly lower (0.25 vs. 6.5 ng/mL, p = 0.004) than those in women who did not present with vaginal bleeding. There were no differences in serum hCG levels (10.5 vs. 3.1 mIU/mL) or serum estradiol levels (65.4 vs. 162.3 pg/mL). After withdrawal bleeding following the first course of EPT, vaginal bleeding was stopped in 27 of the 30 women (90%), and 23 (66%) of all women had a thin and linear endometrium. All women could be treated by up to two courses of EPT and did not require additional interventions. The median duration to hCG normalization after the initial EPT was 24.5 (9-88) days. Conclusion: Women with vascular RPOC who have no bleeding had significantly higher levels of serum progesterone, indicating that administration of progestogen may have an effect on hemostasis. Endometrial bleeding can be prevented or stopped, and retained tissues can be conservatively expelled by oral administration of EPT, including norethisterone, in women with vascular RPOC.